Field Mapping and Modeling of Terrestrial Lava Tube Magnetic Anomalies as an Analog for Lunar Lava Tube Exploration and Prospecting. Issue 6 (30th May 2022) - Bell, Ernest; Schmerr, Nicholas; Young, Kelsey; Esmaeili, Sanaz; Garry, W. Brent; Jazayeri, Sajad; Kruse, Sarah; Richardson, Jacob; Whelley, Patrick
Abstract: Lava tubes are a commonplace feature on the terrestrial planets, and knowledge of tube size and location informs lava flow processes. Future exploration of lava tubes on the Moon can provide access to geologic environments that likely remain unaltered from their emplacement billions of years ago. Lunar lava tubes may also provide astronauts protection from thermal extremes, meteoroid impacts, and radiation. High‐resolution magnetic identification and characterization of lava tubes can be used to help inform future scientific investigations of lava tubes for human exploration and utilization. We demonstrate how magnetometry is useful for determining the geometry and extent of lava tubes on the Earth and, by proxy, the Moon, by relating the magnetic anomalies produced by lava tubes to their location and geomorphology. Using a proton‐precession total field magnetometer, we surveyed an area of more than 100, 000 m 2, with cross‐tube linear traverses spaced at 3–5 m, perpendicular to an approximately 1, 000 m length of the Modoc Crater lava tube complex, within the Lava Beds National Monument (California, USA). The observed magnetic anomalies of the sections known as Incline, Skull, and Ship Caves are compared against synthetic predictions, and the sensitivity of the magnetic anomalies to the tube geometry used to derive a basic relationship between the two. We use our model of terrestrial lava tube magnetic anomalies and adjust for the lunar magnetic environment to predict the signature of anomalies resulting from tubes on the Moon. Plain Language Summary: Lava tubes are caves that can form in flowing lava during volcanic eruptions and are suspected to also exist on the Moon. Lunar lava tubes could provide access to subsurface geologic features that are billions of years old, as well as provide shelter for future human lunar astronauts. Therefore, gaining a better understanding of the locations and sizes of lava tubes will be beneficial to future lunar exploration. Unfortunately, these caves are largely hidden within lava flows. So how can they be located and their size determined? Magnetometry is a geophysical method that uses measurements of magnetic field strengths to map locations of rock units. Solidified lava flows on Earth have magnetic fields that can be detected and quantified by specialized sensors. However, there have been few studies on the magnetic anomalies caused by lava tubes within lava flows. Our research examines the magnetic anomalies of lava tubes within the Lava Beds National Monument. We use observed data and detailed magnetic models to understand the practicality of mapping magnetic anomalies to determine lava tube locations and internal geometries within a lava flow. We also examine the ability to extend these techniques to locating and studying lava tubes on the Moon. Key Points: A lava tube's strongest negative magnetic anomaly is correlated to tube geometry; specifically, cross‐sectional area to depth to center The magnetic minimum gradients of a lava tube magnetic anomaly delineate the spatial position of the walls, indicative of lava tube width Lunar lava tube high spatial resolution magnetic observations can help establish viability for scientific exploration or human utilization